Pendidikan Estetika dari pendekatan Tawhid dan gagasan persuratan baru sebagai model teori Sastera Islam yang ideal cetusan Mohd. Affandi Hassan = An Aesthetic Education of Tawhidic approach and the new narrative paradigm as a model of an ideal theory of Islamic Literature by Mohd Affandi Hassan - Yaacob, Adli (Global Academic Excellence (M) Sdn Bhd (GAE), 2022)
This study relates to the concept of Islamic literature directed by Mohd. Affandi Hassan. He has shown two ideas to explain the concept of his Islamic literature. Firstly, aesthetic education of Tawheed approach, secondly, new writing ideas. In the first place, he emphasized on the nature based on Tawheed that must understand and appreciate the philosophy of the essence of man, the essence of knowledge and charity, as well as the fact and literary function in depth. Next, in order to apply this concept to the students, he introduced a method called KIBLAT to them consisting of reading, understanding, interpreting, enjoying, and composing. Moreover, in the process of composing a work of art, he suggested a new method called ESPEN, a short essay. While in the second ideas of 'New Literature' he emphasized the concept of ihsan and the concept of taklif in producing the masterpiece. Then, Affandi divides the distribution of the work into three stages: First: writing work, second; literary works, third; not valuable/erotic/pornographic works. Through this study, highlights the affirmative personality of Affandi in the field of science, especially literary criticism. Through the 'two ideas' shown by Affandi it is as if the 'Islamic literary concept' has almost reached perfection.